Effects of selected vitamins and minerals on growth rate and hematological parameters in broilers (Asian Journal of Medical and Biological Research, 2016)
The present study was designed with a view to study the body weight and hematological parameters; total erythrocyte count, haemoglobin concentration, packed cell volume and erythrocyte sedimentation rate of growing broilers fed with standard poultry ration. Broilers were kept under close observation for a period of 14 days and body weight was measured at each 7 days interval up to the end of the 35 days of experimental period. A total of 20 (7 days old) broiler chicks were reared throughout the entire period of study. These chicks were randomly divided into four equal groups (n=5). Group A considered as control, fed only standard ration. Group B, C and D was considered as treated group. Group B with vitamin AD3E 1 ml/5 liter drinking water. Group C treated with mineral 1 ml/5 liter dirking water and Group D treated with vitamin (AD3E) 1 ml/5liter and mineral 1 ml/5 liter dirking water with standard ration. It was observed that body weight of broiler increased significantly (p